Algorithm for the Best Uniform Spline Approximation with Free Knots - Vakal, L. P.; Vakal, E. S. (Cybernetics and systems analysis, 2019)
An algorithm for the best uniform approximation by a spline with optimal knots is presented in the paper. Differential evolution is used to find optimal knots. It is one of the best evolutionary algorithms, which sustainably finds function’s global optimum in minimum time. Spline coefficients are computed as a solution of a spline-approximation problem with fixed knots. Results of the numerical experiment are given.